Catamenial Epilepsy - Rabia Gökçen GÖZÜBATIK ÇELİK; Çiğdem ÖZKARA (Archives of Epilepsy, 2018)

(untitled)
When seizures occur in clusters during certain stages of the menstrual cycle (perimenstrual and periovulatory stages), it is defined as catamenial epilepsy. The prevalence varies between 10% and 70%. There are 3 patterns of catamenial epilepsy: perimenstrual (most common), periovulatory, and seizures in the insufficient luteal phase. In the pathophysiology of this occurrence, the neuroactive properties of the reproduction-associated steroid hormones (direct membrane-associated short-term effect and intracellular receptor/genomic-related longterm effect) and their cyclic changes in serum levels play a role in the susceptibility of the epileptogenic area to neuroactive steroids. Among steroid hormones, while progesterone and neurosteroids are known as anticonvulsants, estrogen, the best known proconvulsant, has been found in recent studies to also have anticonvulsant effects related to Neuropeptide Y. Hormonal (medroxyprogesterone acetate, clomiphene, triptorelin, leuprolide, progesterone, goserelin), non-hormonal (acetazolamide, clobazam, lamotrigine, levetiracetam), and neurosteroidbased therapies (ganaxolone) are used in the treatment of catamenial epilepsy. Seizure control and menstrual cycle maintenance, measurement of the blood level of antiepileptic drugs before and after menstruation and adjustment of the drug dosage as required, intermittent benzodiazepine administration, acetazolamide, or hormonal treatments such as oral contraceptives during menstruation are among the treatment strategies for catamenial epilepsy.